Caracterização fitossociológica das bromeliaceas epifíticas e suas relaçoes com os fatores geomorfologicos e pedologicos da planície do rio Iguaçu, Paraná, Brasil - Bonnet, Annete (2013)
The forests of the Iguaçu river floodplain, which are part of two distinct phytogeographic units, Mixed Ombrophillous Forest and Semidecidual Seasonal Forest, are currently very modified. This alteration occurred due to historical factors and contemporaneous anthropic action. Epiphytic bromeliads, due to its specific substrate dependence and its strategy to obtain nutrients through their trichomes, are considered indicators of environmental condition alterations. Taking into account the reduced amount of research using this approach and the inexistence of systematic and continuous works with bromeliads along Brazilian's rivers, it was studied the floristic and the structure of the forests, and the communities of bromeliads present on aggradation and degradation surfaces of the compartments established from the first until the third highland of Paraná. In each area, the qualitative and quantitative data of bromeliads were related to the physical factors of the environment, like streambed type, height of the border, predominant geomorphic sites and soil water saturation. It was registered a total of 14 species of bromeliads belonging to six genera, which presented significant differences in diversity and abundance among the compartments. Macroclimate was the most important factor to define the differences between the two phytogeographic units, besides the conservation state of the forest which was a very changeable characteristic among the surfaces. Locally, bromeliads reacted to the high taxes of atmosphere humidity, created by the proximity of the river, by the existence of geomorphic concaved sites and by soils with low permeability that make possible the accumulation of water. They reacted also to the stratification of the forest and the presence of high trees that represent more surface and longer time of exposition of the substrate for the colonization. On phorophytes, the bromeliads occurred in intervals of very varied heights, indicating that the small height of the forest and the existence of forest gaps created by the presence of the river and the presence of soils containing high content of water, influenced the vertical stratification standard. Seedlings could be related to the amount and diversity of existing adults in the area, as well as, to the available environmental humidity. The beginning of the crown was the local of establishment of tank bromeliads and zoochoric bromeliads. This could be related to the biggest weight of the individuals and to the place of landing of avian dispersers. Aechmea recurvata, Wittrockia cyathiformis and Billbergia nutans, beyond Vriesea reitzii, were chosen as indicators of vegetation in advanced state of regeneration. Beside that, Aechmea distichantha, Tillandsia tenuifolia, Tillandsia usneoides and Vriesea friburgensis were considered the pioneers in the occupation of trees that grow in the most recent sediments of the aggradation surfaces. T. usneoides showed to be the most important element for mapping the humid environment in the lowland, but only in open places, where the evaporation and the humidity removal are constant.